Molecular Verification of New World Mansonella perstans Parasitemias - Lucyane Bastos Tavares da Silva; James Lee Crainey; Túllio Romão Ribeiro da Silva; Uziel Ferreira Suwa; Ana Carolina Paulo Vicente; Jansen Fernandes de Medeiros; Felipe Arley Costa Pessoa; Sérgio Luiz Bessa Luz (Emerging Infectious Diseases, 2017)
We obtained ribosomal and mitochondrial DNA sequences from residents of Amazonas state, Brazil, with Mansonella parasitemias. Phylogenetic analysis of these sequences confirm that M. ozzardi and M. perstans parasites occur in sympatry and reveal the close relationship between M. perstans in Africa and Brazil, providing insights into the parasite’s New World origins.